A mobile health intervention for weight management among young adults: a pilot randomised controlled trial. Issue 4 (29th August 2013) - Hebden, L.; Cook, A.; van der Ploeg, H. P.; King, L.; Bauman, A.; Allman‐Farinelli, M.
Abstract Background Today's generation of young adults are gaining weight faster than their parents; however, there remains insufficient evidence to inform interventions to prevent this weight gain. Mobile phones are a popular means of communication that may provide a convenient, inexpensive means to deliver health intervention programmes. This pilot study aimed to measure the effect of a 12‐week mobile health (mHealth) intervention on body weight, body mass index and specific lifestyle behaviours addressed by the programme. Methods University students and staff aged 18–35 years (n = 51) were randomised (ratio 1 : 1, intervention : control). Both groups received a printed diet booklet with instructions prepared by a dietitian. The intervention group also received Short Message Service (SMS) text messages (four per week), e‐mails (four per week), and had access to smartphone applications and Internet forums. Results Pre‐ to post‐intervention, participants in the intervention group decreased their body weight [mean (SD)] [−1.6 (2.6) kg], increased their light intensity activity [34 (35) min day−1] and reported an increased vegetable (1.0 median serving day−1) and decreased sugar‐sweetened beverage intake [−355 (836) mL week−1]. Despite this, post‐intervention changes in outcomes were not significantly different from controls. Conclusions The piloted mHealth programme provided some short‐term positive changes in weight, nutrition and physical activity using a low cost, convenient delivery method for this population. However, changes were no different from those observed among controls. This might partly be explained by intervention participants' low engagement with the programme, which is likely to require further modification to provide more regular, personalised, monitored support.